(untitled) (Philological Studies, 2023)
The paper analyzes the expressionist portrait of Peter II Petrović Njegoš, which Stanislav Vinaver presented in the essay “Njegoš and the Evil Wizards” (Gromobran svemira, 1921). In order to understand this particular vision of the romantic poet, the immediate historical proximity of Crnjanski’s Njegoš from 1919 (the poem “Njegoš”, Lyrics of Ithaka), then his Njegoš from 1925 (the essay “Reflections on Njegoš”), and finally Andrić’s Njegoš in the essay “Njegoš as a tragic hero of Kosovo thought” (1935). As the neglected texts of previous Njegosology, today, at a time when Njegoš’s character and work have become a singular Balkan apple of discord, they show another way of understanding, and that is the way of utopian thinking.